2016
DOI: 10.1007/s40808-016-0257-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of climate change on surface hydrological processes using SWAT: a case study of Omo-Gibe river basin, Ethiopia

Abstract: In the present study, an ArcSWAT model was utilized to simulate the hydrological responses due to land use and climatic changes in the Omo-Gibe river basin, Ethiopia. The performance of the model was evaluated through sensitivity, uncertainty analysis, calibration and validation. The most sensitive parameters were identified which are governing on surface runoff generation processes in the selected basin. The calibration and validation of the model was done using SWAT-2005. Also, the sensitivity and uncertaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 10 publications
2
25
0
1
Order By: Relevance
“…This model simulates the production of water and sediments in large-scale watersheds, complex basins, with various soil types, land uses and management conditions; it also simulates the effect of agronomic practices or any other activity on water quality [12,13]. It has been used in various situations, especially in areas known for their environmental vulnerability [14]. The model has proven efficiency in semi-arid conditions in many cases over the world (California, Mexico, Spain, Morocco, Tunisia, Iran, Italy…) [15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This model simulates the production of water and sediments in large-scale watersheds, complex basins, with various soil types, land uses and management conditions; it also simulates the effect of agronomic practices or any other activity on water quality [12,13]. It has been used in various situations, especially in areas known for their environmental vulnerability [14]. The model has proven efficiency in semi-arid conditions in many cases over the world (California, Mexico, Spain, Morocco, Tunisia, Iran, Italy…) [15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of sedimentation is aggravated by human activities and climate change. A study conducted by Belete [7] on Lake Hawasa showed that sedimentation caused the rise in the lake's level.The effects of climate change on water resources have been widely studied [8][9][10][11][12][13]. However, such potential effects on sediment yield have received comparatively little attention.…”
mentioning
confidence: 99%
“…The effects of climate change on water resources have been widely studied [8][9][10][11][12][13]. However, such potential effects on sediment yield have received comparatively little attention.…”
mentioning
confidence: 99%
“…Correction factors were computed from the statistics of the observed and the simulated variables. The principle of this method shows the mean and the standard deviation of the daily precipitation data becoming equal to those of the observed data [59][60][61].…”
Section: Bias Correction Methodsmentioning
confidence: 99%